2021
DOI: 10.1134/s0006297921120075
|View full text |Cite
|
Sign up to set email alerts
|

Role of Innate Immunity and Oxidative Stress in the Development of Type 1 Diabetes Mellitus. Peroxiredoxin 6 as a New Anti-Diabetic Agent

Abstract: The review discusses information on the development of type 1 diabetes mellitus (T1D) as a systemic autoimmune and inflammatory disease. Focus of the review is on the role of innate immune system, including activation of some signal ing cascades, cytokine response, and activity of the Toll like receptors in the development of T1D. Dysfunction of innate immunity is the cause of the attack of pancreatic beta cells by the host T lymphocytes, which leads to the death of pancre atic beta cells that produce insulin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 95 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…We have previously demonstrated the protective role of exogenous peroxiredoxin 6 under T1D conditions in a diabetic mouse model and in a rat insulinoma RIN-m5F β-cell model [12][13][14]. In addition, we have recently discussed the role of senescent β-cells in the development of type 1 diabetes, in which we concluded that peroxiredoxin 6 can be qualified as a new protective and senolytic agent in diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 89%
“…We have previously demonstrated the protective role of exogenous peroxiredoxin 6 under T1D conditions in a diabetic mouse model and in a rat insulinoma RIN-m5F β-cell model [12][13][14]. In addition, we have recently discussed the role of senescent β-cells in the development of type 1 diabetes, in which we concluded that peroxiredoxin 6 can be qualified as a new protective and senolytic agent in diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, the insulin-stimulating activity of Prx6 in vitro was detected both when RIN-m5F β-cells were cultivated under normal conditions and under stressful conditions, inducing cell death [99]. In an alloxan-or streptozotocin-induced mouse model of diabetes, intravenous administration of recombinant Prdx6 prevented hyperglycemia, reduced mortality, restored the plasma cytokine profile, and reduced β-cell destruction in the islets of Langerhans in the mouse pancreas [100][101][102].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Diabetes mellitus (DM) remains a serious medical and social problem throughout the world. Oxidative stress and impaired DNA repair are important factors in the development of DM and its complications (Ramani et al, 2020;Novoselova et al, 2021;Kopf et al, 2021). DNA repair enzymes are chosen as targets for antidiabetic therapies (Sarras et al, 2014;Abdelali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%